2018
DOI: 10.11114/jets.v6i6.3103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Somatotype Characteristics and Anthropometric Proportional Relations of Elite Wrestlers Between Styles and Weights

Abstract: In this paper, comparison of somatotype characteristics and anthropometric proportional relations of elite wrestlers at the level of styles and weights and, contribution to improvement and orientation of sport is aimed. 57 elite wrestlers took place in the European Championship Preparatory Camp of Turkish National Adults Wrestling Team (31 greco-roman style with 7 light weight, 14 medium weight and 10 heavy weight -with av. height: 168.9 cm. and av. weight: 81.1 kg.; 26 free style with 8 light weight, 12 are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Sterkowicz-Przybycień et al [48] calculated the somatotype of 23 elite Polish male wrestlers as 1.7-6.3-1.3 in light weight and 2.2-6.8-1.1 in heavy weight, and the endomorphic component increased significantly. Öcal Kaplan and Yıldıran [39] reported the somatotype mean of 57 elite Turkish wrestlers aged 23.35 as 2.15-6.14-1.17 in light weight, 2.59-6.70-0.75 in middle weight, 4.12-7.90-0.18 in heavy weight. Noh et al [34] calculated the somatotypes of 13 elite Korean wrestlers with an mean age of 19.5 according to weight categories as 1.6-3.6-2.7 in light weight, 2.8-5.3-0.7 in middle weight, 3.7-5.9-0.3 in heavy weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sterkowicz-Przybycień et al [48] calculated the somatotype of 23 elite Polish male wrestlers as 1.7-6.3-1.3 in light weight and 2.2-6.8-1.1 in heavy weight, and the endomorphic component increased significantly. Öcal Kaplan and Yıldıran [39] reported the somatotype mean of 57 elite Turkish wrestlers aged 23.35 as 2.15-6.14-1.17 in light weight, 2.59-6.70-0.75 in middle weight, 4.12-7.90-0.18 in heavy weight. Noh et al [34] calculated the somatotypes of 13 elite Korean wrestlers with an mean age of 19.5 according to weight categories as 1.6-3.6-2.7 in light weight, 2.8-5.3-0.7 in middle weight, 3.7-5.9-0.3 in heavy weight.…”
Section: Discussionmentioning
confidence: 99%
“…Also, weight categories are an important factor to determining the morphological differentiation of wrestlers. The biggest somatotype differences among weight categories occur between the heavy weight and light weight [8,9,23,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of anthropological parameters that allow the assignment of a competitor to a specific sports discipline can be very helpful for discipline-specific achievements. Several studies reported that anthropometric parameters for different age groups and sports disciplines [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] could be split into two based on the reported parameters. These are [2] purely anatomical, anthropometric reports providing lengths and widths of limps and circumferences of the chest and waist and [4] fitness-related anthropometric reports that include bone mineral density (BMD) and free-fat mass (FFM).…”
Section: Introductionmentioning
confidence: 99%
“…Bu farklılıklar ağırlık kategorisi olan güreş ve halter gibi branşların sıkletleri arasında gözlenmektedir. Genel olarak ağırlık kategorisi yükseldikçe sporcuların vücut yağ oranı artmaktadır (Keogh vd., 2007;Garcia-Pallares vd., 2011;Öcal Kaplan ve Yıldıran, 2018). Buna karşın, sporcuların seviyeleri ve performansları arttıkça da vücut yağ yüzdelerinde azalma gözlenmektedir (Behdari vd., 2016).…”
Section: Introductionunclassified